Design of organization construction for diplomatic complexes - B S Istomin; A D Razin (RUDN Journal of Engineering Research, 2014)
The article deals with specific methods and rules for planning organization construction diplomatic complexes. The article analyses contents and parts of design of organization construction, terms of construction, distinguished character of some kinds of buildings works in preparatory period. In the article definitions the directions in decision of the problem calculate terms of buildings in different periods of building the diplomatic objects.